Peer Relationships with Achievement Events: Cross Sectional Approach - Pipitcahyani, Tatarini; Husni, Ervi; Isfentiani, Dina; Hafid, Fahmi; Sa’diyah, Halimatus Sa’diyah (YCAB Publisher, 2025)
Background: Peer relationships are formed through interactions that occur both at home and in educational settings. Adolescents often function as sources of advice, motivation, and behavioral modeling for their peers, which can significantly influence individual attitudes and behaviors. The quality of these peer relationships is closely associated with students' academic achievement. Adolescents are expected to develop self-regulatory skills to minimize learning gaps and avoid negative learning attitudes. Objective: This study aims to examine the influence of peer relationships on the academic achievement of female students. Method: The study employed an analytical survey design with a cross-sectional approach, involving 70 respondents. Data were analyzed using the Chi-Square test, with a significance level set at p < 0.05. Results: The Fisher's Exact Test yielded p-values of 0.023 and 0.05, indicating a statistically significant association between peer relationships and the academic achievement of female students. Conclusion: This study recommends the inclusion of additional variables and a broader research scope in future studies to strengthen the findings. Female students are encouraged to build peer relationships with individuals who can serve as academic motivators, thereby fostering continuous improvement in their academic performance. Keywords: peer relationships; academic achievement; female students; Indonesia